2002
DOI: 10.1093/nar/gnf080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RNA flexibility by scanning force spectroscopy

Abstract: Scanning force spectroscopy was used to measure the mechanical properties of double stranded RNA molecules in comparison with DNA. We find that, similar to the B-S transition in DNA, RNA molecules are stretched from the assumed A' conformation to a stretched conformation by applying a defined force (plateau force). The force depends on the G + C content of the RNA and is distinct from that required for the B-S transition of a homologous DNA molecule. After the conformational change, DNA can be further extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…S2B) and an overstretching transition for torsionally unconstrained molecules (SI Appendix, Fig. S2C), in agreement with previous single-molecule studies (16,17). From fits of the extensible WLC model, we found S RNA = 350 ± 100 pN, about threefold lower than S DNA (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…S2B) and an overstretching transition for torsionally unconstrained molecules (SI Appendix, Fig. S2C), in agreement with previous single-molecule studies (16,17). From fits of the extensible WLC model, we found S RNA = 350 ± 100 pN, about threefold lower than S DNA (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 90%
“…1A). Although recent single-molecule stretching experiments using torsionally unconstrained dsRNA have revealed its bending persistence length (15,16), stretch modulus (16), and an overstretching transition (16,17), its response to torsional strains and structural transitions under forces and torques is unknown. This dearth of information on dsRNA is partially due to the relative difficulty, compared with dsDNA, of assembling RNA constructs suitable for single-molecule force and torque measurements.…”
mentioning
confidence: 99%
“…Early studies indicated a large persistence length of RNA when compared with DNA (1), that is that RNA is more rigid than DNA. This is still largely the view which was supported by single molecule (2,3) and atomic force microscopy (AFM) measurements (4). On a base pair level, that is, on a microscopic scale, most of our knowledge comes from molecular dynamic simulations (5–8).…”
Section: Introductionmentioning
confidence: 91%
“…The forces were similar to those employed in earlier studies on viruses 46,53,54 and biological crystals. [55][56][57] There is considerable previous AFM work concerning double-stranded DNA 49,58,59 but, with some exceptions, 58,[60][61][62] rather little on single-stranded RNA. Before investigating single-stranded RNA, DNA plasmids pET19B (Sigma Biochemical Co. St. Louis, MO) were spread on mica and imaged.…”
Section: Afm Proceduresmentioning
confidence: 99%